2009
DOI: 10.1002/ptr.2929
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid protects against ischemia/reperfusion‐induced renal damage and inhibits leukocyte apoptosis

Abstract: The possible protective effect of betulinic acid on renal ischemia/reperfusion (I/R) injury was studied. Wistar Albino rats were unilaterally nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 6 h of reperfusion. Betulinic acid (250 mg/kg, i.p.) or saline was administered at 30 min prior to ischemia and immediately before the reperfusion. Creatinine, blood urea nitrogen (BUN), lactate dehydrogenase (LDH) and TNF-α as well as the oxidative burst of neutrophil and leukocyte apoptosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Triterpenoids are ubiquitous in plants and have long been considered to be the anti-inflammatory principles in several herbal drugs [14]. Betulinic acid (BA), (3b-hydroxy-lup-20(29)-en-28-oic acid is a naturally occurring pentacyclic lupane group triterpenoid.…”
Section: Introductionmentioning
confidence: 99%
“…Triterpenoids are ubiquitous in plants and have long been considered to be the anti-inflammatory principles in several herbal drugs [14]. Betulinic acid (BA), (3b-hydroxy-lup-20(29)-en-28-oic acid is a naturally occurring pentacyclic lupane group triterpenoid.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vivo studies on bacterial lipopolysaccharide-induced lung damage demonstrated the anti-inflammatory and anti-oxidant properties of 2 at oral doses as small as 25 mg/kg [20]. The therapeutic potential of 2 in oxidative damage has also been established as protection from ischemia/reperfusion-induced renal damage was reported [21]. Similarly, the induction of NF-κB activation by carcinogens has been shown to be suppressed by 2 through inhibition of IκBα kinase and p65 phosphorylation as well as abrogation of cyclooxygenase-2 and matrix metalloprotease-9 [22].…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, in the betulinic acid treated colitis groups, MPO activities were decreased. The effects of betulinic acid on MPO activity were previously studied by Ekşioğlu-Demiralp et al (9) where the authors demonstrated that ischemia reperfusioninduced elevation of MPO in renal tissues was reduced by betulinic acid treatment. Furthermore, as assessed by the colonic collagen content, our findings suggest that betulinic acid may have an additional protective effect by inhibiting the production and deposition of extracellular matrix components that result in tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since triterpenoids have a similarity to steroidal compounds, their effects have often been attributed to a mechanism related to antiinflammatory action. In our previous study we have demonstrated that betulinic acid attenuates ischemia/reperfusion-induced oxidant responses and improved renal function by regulating apoptotic function of leukocytes and inhibiting neutrophil infiltration (9).…”
Section: Introductionmentioning
confidence: 99%